Emodin Inhibits the Proliferation of MCF-7 Human Breast Cancer Cells Through Activation of Aryl Hydrocarbon Receptor (AhR) - Zhang, Ning; Wang, Jiawen; Sheng, Aimin; Huang, Shuo; Tang, Yanyan; Ma, Shitang; Hong, Ge (Frontiers in Pharmacology, 2021)
Natural products have proved to be a promising source for the development of potential anticancer drugs. Emodin, a natural compound from Rheum palmatum, is used to treat several types of cancers, including lung, liver, and pancreatic. However, there are few reports regarding its use in the treatment of breast cancer. Thus, the therapeutic effect and mechanism of emodin on MCF-7 human breast cancer cells were investigated in this study. Morphological observations and cell viability were evaluated to determine the anti-proliferation activity of emodin. Network pharmacology and molecular docking were performed to screen the potential targets. Western blot analysis was used to explore a potential antitumor mechanism. The results showed that emodin (50–100 μmol/L) could significantly inhibit the proliferation of MCF-7 cells in a time and dose-dependent manner. Furthermore, virtual screening studies indicated that emodin was a potent aryl hydrocarbon receptor (AhR) agonist in chemotherapy for breast cancer. Finally, when MCF-7 cells were treated with emodin (100 μmol/L) for 24 h, the AhR and cytochrome P450 1A1 (CYP1A1) protein expression levels were significantly upregulated compared with the control group. Our study indicated that emodin exhibited promising antitumor activity in MCF-7 cells, likely through activation of the AhR-CYP1A1 signaling pathway. These findings lay a foundation for the application of emodin in breast cancer treatment.